Skopje: Time, Narrative, and Politics - Rancière, Jacques; Burk, Drew S. (Identities: Journal for Politics, Gender and Culture, 2015)
I would like to recall several ideas that have supported the entirety of my work for the past 40 years: forms of worker emancipation and the regimes of the identification of art; the transformations of literary fiction and the principles of democracy; the presuppositions of historical science and the forms of consensus by today’s dominant apparatuses. What unites all these areas of research is the attention to the way in which these practices and forms of knowledge imply a certain cartography of the common world. I have chosen to name this system of relations between ways of being, doing, seeing, and thinking that determine at once the common world and the ways in which everyone takes part within it the “distribution of the sensible.” But it must also be said that temporal categories play an important role in this as well. By defining a now, a before and an after, and in connecting them together within the narrative, they predetermine the way in which the common world is given to us in order to perceive it and to think it as well as the place given to everyone who occupies it and the capacity by which each of us then has to perceive truth. The narrative of time at once states what the flow of time makes possible as well as the way in which the inhabitants of time can grasp (or not grasp) these “possibles.” This articulation is a fiction. In this sense, politics and forms of knowledge are established by way of fictions including as well works that are deemed to be of the imagination. And the narrative of time is at the heart of these fictions that structure the intelligibility of these situations, which is to say as well, their acceptability. The narrative of time is always at the same time a fiction of the justice of time. Author(s): Jacques Rancière Title (English): Skopje: Time, Narrative, and Politics Translated by (French to English): Drew S. Burk Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 7-18 Page Count: 11 Citation (English): Jacques Rancière, “Skopje: Time, Narrative, and Politics,” translated from the French by Drew S. Burk, Identities: Journal for Politics, Gender and Culture, Vol. 11, No. 1 (Summer 2015): 7-18.